The Role of Social Media in Health Promotion Efforts - Nurul Fadhilah (PT. Anagata Sembagi Education, 2024)
The incidence of disease in Indonesia follows or even exceeds the rate of population growth. Every second, Indonesians suffer from diseases that do not necessarily have effective treatments. It is important to realize that waiting for symptoms to appear before seeking health care is risky. While hospitals have made efforts to promote health and prevent disease, their role in providing health information is limited. The information provided by doctors and medical institutions often does not cover all relevant factors. In the era of rapid information technology, the need for precise and up-to-date information is increasingly becoming a priority. Communities and public institutions are beginning to utilize technology, especially the internet, to gain better access to health information. However, uncontrolled distribution of information can trigger new problems. Therefore, it is important to have organized, clear and precise information to support effective decision-making. An analysis of the potential of online media as a tool to change health behavior is necessary, especially with the widespread penetration of the internet through various devices, including smartphones and tablets.